2007
DOI: 10.1103/physrevb.76.184425
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and thermalization of the nuclear spin bath in the single-molecule magnetMn12ac: Test for the theory of spin tunneling

Abstract: The description of the tunneling of a macroscopic variable in the presence of a bath of localized spins is a subject of great fundamental and practical interest, and is relevant for many solid-state qubit designs. Most of the attention is usually given to the dynamics of the "central spin" (i.e., the qubit), while little is known about the spin bath itself. Here we present a detailed study of the dynamics of the nuclear spin bath in the Mn12-ac single-molecule magnet, probed by NMR experiments down to very low… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 83 publications
(275 reference statements)
2
20
0
Order By: Relevance
“…the influence of quantum tunneling of the nanomagnets on the nuclear spin dynamics, was observed short thereafter for 1 H [43] and 57 Fe in Fe 8 [4], and 55 Mn in Mn 12 [25,27] [Fig. 3(c)].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…the influence of quantum tunneling of the nanomagnets on the nuclear spin dynamics, was observed short thereafter for 1 H [43] and 57 Fe in Fe 8 [4], and 55 Mn in Mn 12 [25,27] [Fig. 3(c)].…”
Section: Resultsmentioning
confidence: 99%
“…that it should be strongly suppressed by a longitudinal external field. Indeed, it has been observed that the nuclear T 1 in Mn 12 at very low temperatures becomes almost two orders of magnitude slower with the application of a small longitudinal field [25,27], as compared to the zero-field case [ Fig. 3(d)].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations